2022
DOI: 10.3389/fpsyg.2022.993381
|View full text |Cite
|
Sign up to set email alerts
|

Going beyond the DSM in predicting, diagnosing, and treating autism spectrum disorder with covarying alexithymia and OCD: A structural equation model and process-based predictive coding account

Abstract: BackgroundThere is much overlap among the symptomology of autistic spectrum disorders (ASDs), obsessive compulsive disorders (OCDs), and alexithymia, which all typically involve impaired social interactions, repetitive impulsive behaviors, problems with communication, and mental health.AimThis study aimed to identify direct and indirect associations among alexithymia, OCD, cardiac interoception, psychological inflexibility, and self-as-context, with the DV ASD and depression, while controlling for vagal relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 166 publications
2
3
0
Order By: Relevance
“…Further analyses by Mul et al (2018) and Yang et al (2021) indicated that reduced interoceptive processing in individuals with ASD was linked to decreased self-reported IA, affecting their capacity to recognize bodily sensations and, by extension, identify and articulate emotions. These outcomes align with Edwards (2022) , who explored causal relationships involving alexithymia, obsessive-compulsive disorder (OCD), and ASD, discovering significant connections with IA, notably through the subscale of Self-Regulation. Furthermore, Edwards’ study revealed that IA, particularly the Attention Regulation subscale, could partially mediate the association between OCD and ASD, suggesting indirect pathways linking alexithymia and OCD with ASD severity via IA ( Edwards, 2022 ).…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…Further analyses by Mul et al (2018) and Yang et al (2021) indicated that reduced interoceptive processing in individuals with ASD was linked to decreased self-reported IA, affecting their capacity to recognize bodily sensations and, by extension, identify and articulate emotions. These outcomes align with Edwards (2022) , who explored causal relationships involving alexithymia, obsessive-compulsive disorder (OCD), and ASD, discovering significant connections with IA, notably through the subscale of Self-Regulation. Furthermore, Edwards’ study revealed that IA, particularly the Attention Regulation subscale, could partially mediate the association between OCD and ASD, suggesting indirect pathways linking alexithymia and OCD with ASD severity via IA ( Edwards, 2022 ).…”
Section: Resultssupporting
confidence: 60%
“…These outcomes align with Edwards (2022) , who explored causal relationships involving alexithymia, obsessive-compulsive disorder (OCD), and ASD, discovering significant connections with IA, notably through the subscale of Self-Regulation. Furthermore, Edwards’ study revealed that IA, particularly the Attention Regulation subscale, could partially mediate the association between OCD and ASD, suggesting indirect pathways linking alexithymia and OCD with ASD severity via IA ( Edwards, 2022 ).…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations